Analysis the Active Voice in Moi Language (The Structure of Moi Sentences) - Anakotta, Raisa; Sudibyo, Doni; Ataya, Hermina (INTERACTION: Jurnal Pendidikan Bahasa, 2019)
The study about linguistic in Papua with English were analyzed How the word arrange in Positive, negative and Interrogative sentences. This study is about Active Voice in Moi language. The researcher attempted to find some Active sentences in Moi language and try to analysis. She also classified the verb based on the subject and also explains the uniqueness by words. This study used descriptive linguistic research to analyze. The researcher offered numerous recommendations and suggestions.